Criptovalute e Halachà: uno status giuridico ancora da chiarire - Gardella Tedeschi, Bianca (La moneta di Dio, 2022)
Is it possible to consider to be currency something whose value depends solely on supply and demand instead of being guaranteed by a state, its reserves and its central bank? Cryptocurrencies want to achieve this by creating a currency, bitcoins, that can operate in the absence of a bank. And, with ups and downs, the feat has succeeded. Today important economic transactions are traded in bitcoin, and this «currency» has become increasingly important. Even religious laws, and Jewish law is among them, have wondered what’s the proper place for cryptocurrencies, whether a real currency or otherwise. In this article, we want to give an overview of the birth and functioning of cryptocurrencies, highlighting the characteristics that the Halacha considers essential for their recognition and legal classification.